Casein Supplementation Does Not Affect the Estimates of True Total Tract Digestibility of Phosphorus in Soybean Meal for Growing Pigs Determined by the Regression Method - J. B. Liu; O. Adeola (Asian-Australasian Journal of Animal Sciences, 2016)
Forty-eight barrows with an average initial body weight of 25.5±0.3 kg were assigned to 6 dietary treatments arranged in a 3×2 factorial of 3 graded levels of P at 1.42, 2.07, or 2.72 g/kg, and 2 levels of casein at 0 or 50 g/kg to compare the estimates of true total tract digestibility (TTTD) of P in soybean meal (SBM) for pigs fed diets with or without casein supplementation. The SBM is the only source of P in diets without casein, and in the diet with added casein, 1.0 to 2.4 g/kg of total dietary P was supplied by SBM as dietary level of SBM increased. The experiment consisted of a 5-d adjustment period and a 5-d total collection period with ferric oxide as a maker to indicate the initiation and termination of fecal collection. There were interactive effects of casein supplementation and total dietary P level on the apparent total tract digestibility (ATTD) and retention of P (p<0.05). Dietary P intake, fecal P output, digested P and retained P were increased linearly with graded increasing levels of SBM in diets regardless of casein addition (p<0.01). Compared with diets without casein, there was a reduction in fecal P in the casein-supplemented diets, which led to increases in digested P, retained P, ATTD, and retention of P (p<0.01). Digested N, ATTD of N, retained N, and N retention were affected by the interaction of casein supplementation and dietary P level (p<0.05). Fecal N output, urinary N output, digested N, and retained N increased linearly with graded increasing levels of SBM for each type of diet (p<0.01). The estimates of TTTD of P in SBM, derived from the regression of daily digested P against daily P intake, for pigs fed diets without casein and with casein were calculated to be 37.3% and 38.6%, respectively. Regressing daily digested N against daily N intake, the TTTD of N in SBM were determined at 94.3% and 94.4% for diets without casein and with added casein, respectively. There was no difference in determined values of TTTD of P or N in SBM for pigs fed diets with or without casein (p>0.05). In summary, our results demonstrate that the estimates of TTTD of P in SBM for pigs were not affected by constant casein inclusion in the basal diets.